Autonomous localization of partial discharge sources within large transformer windings - Rahman M.S.A.; Lewin P.L.; Rapisarda P. (Institute of Electrical and Electronics Engineers Inc., 2023)
Condition monitoring; Digital radio; Impulse response; Partial discharges; Power transformers; Principal component analysis; Signal processing; Wavelet transforms; Winding; Different frequency; Electrical detection method; Health informations; Monitoring hardware; Partial discharge sources; Power transformer insulation; Radio frequency current transducer; Source localization; Transformer windings